Expressing antigen binding fragments with high titers in a targeted integration CHO host by optimizing expression vector gene copy numbers and position: A case study. (16th August 2022) - Tang, Danming; Gunson, Jane; Tran, Eric; Lam, Cynthia; Shen, Amy; Snedecor, Brad; Barnard, Gavin; Misaghi, Shahram
Abstract: Antigen binding fragments (Fab) are a promising class of therapeutics as they maintain high potency while having significantly smaller size relative to full‐length antibodies. Because Fab molecules are aglycosylated, many expression platforms, including prokaryotic, yeast, and mammalian cells, have been developed for their expression, with Escherichia coli being the most commonly used Fab expression system. In this study, we have examined production of a difficult to express Fab molecule in a targeted integration (TI) Chinese Hamster Ovary (CHO) host. Without a need for extensive host or process optimization, as is usually required for E. coli, by simply using different vector configurations, clones with very high Fab expression titers were obtained. In this case, by increasing heavy chain (HC) gene copy numbers, clones with titers of up to 7.4 g/L in the standard fed‐batch production culture were obtained. Our findings suggest that having a predetermined transgene integration site, as well as the option to optimize gene copy number/dosage, makes CHO TI hosts an effective system for expression of Fab molecules, allowing Fab expression using platform process and without significant process development efforts.